Burden of influenza, healthcare seeking behaviour and hygiene measures during the A(H1N1)2009 pandemic in France: a population based study - Van Cauteren Dieter; Vaux Sophie; de Valk Henriette; Le Strat Yann; Vaillant Véronique; Lévy-Bruhl Daniel (BMC Public Health, 2012)
Abstract Background Influenza surveillance systems do not allow the identification of the true burden of illness caused by influenza in the community because they are restricted to consulting cases. A study was conducted to estimate the incidence and the burden of self-defined influenza, and to describe healthcare seeking behavior for self-defined influenza during the A(H1N1)2009 pandemic in the French population. Methods We conducted a random-based retrospective cross-sectional telephone survey between May 2009 and April 2010 among a random sample of the French population. Results For the 10 076 people included, 107 episodes of self-defined influenza were reported. The annual incidence of self-defined influenza was estimated at 13 942 cases per 100 000 inhabitants (CI95% 10 947 – 16 961), 62.1% (CI95% 50.5 – 72.5) of cases consulted a physician and 11.3% (CI95% 5.5 - 21.7) used a face mask. Following recommendations, 37.5% (CI95% 35.5 – 39.5) of people in the survey reported washing their hands more often during the pandemic season, and there was a positive association with being vaccinated against A(H1N1)2009 influenza, being a women, being a child (< 15 years) or living in a big city (≥ 100 000 inhabitants). Conclusions Self-defined influenza causes a significant burden of illness in the French population and is a frequent cause for consultation. These results allow a more accurate interpretation of influenza surveillance data and an opportunity to adapt future health education messages.